2011
DOI: 10.1186/1752-1947-5-516
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant DNA methylation of cancer-related genes in giant breast fibroadenoma: a case report

Abstract: IntroductionGiant fibroadenoma is an uncommon variant of benign breast lesions. Aberrant methylation of CpG islands in promoter regions is known to be involved in the silencing of genes (for example, tumor-suppressor genes) and appears to be an early event in the etiology of breast carcinogenesis. Only hypermethylation of p16INK4a has been reported in non-giant breast fibroadenoma. In this particular case, there are no previously published data on epigenetic alterations in giant fibroadenomas. Our previous res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Based on this, specific aberrant DNA methylation patterns have been proposed as predictive and prognostic markers for several cancer types (Okugawa et al 2015 ; D'Errico et al 2020 ; Singh et al 2019 ; Almeida et al 2019 ). Specifically, in breast cancer, previous work of our group has identified that the DNA methylation profiles of tumor suppressor genes correlate with prognosis index (Marzese et al 2010 , 2012 ), with tumor subtypes (Branham et al 2012 ), migration and metastasis capacity (Urrutia et al 2015 ; Marzese et al 2014 ), benign mammary lesions (Marzese et al 2011 ), and, more relevant for the topic of this study, with the laterality of the tumors (Campoy et al 2016 ). In summary, tumor epigenome is influenceable by the microenvironment and can be associated with differential tumor behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this, specific aberrant DNA methylation patterns have been proposed as predictive and prognostic markers for several cancer types (Okugawa et al 2015 ; D'Errico et al 2020 ; Singh et al 2019 ; Almeida et al 2019 ). Specifically, in breast cancer, previous work of our group has identified that the DNA methylation profiles of tumor suppressor genes correlate with prognosis index (Marzese et al 2010 , 2012 ), with tumor subtypes (Branham et al 2012 ), migration and metastasis capacity (Urrutia et al 2015 ; Marzese et al 2014 ), benign mammary lesions (Marzese et al 2011 ), and, more relevant for the topic of this study, with the laterality of the tumors (Campoy et al 2016 ). In summary, tumor epigenome is influenceable by the microenvironment and can be associated with differential tumor behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Hypermethylation at the promoter region of several genes has been shown to be an important mechanism in gene silencing. However, gene-acquired methylation may not necessarily be related with malignant phenotype [ 16 , 17 ]. In this report, we show that a gastric leiomyoma, considered a benign disease, presents methylation in 2–5 of 84 analyzed CpGI, varying in different tumor parts.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have proved that epigenetic changes of multiple TSGs (tumor suppressor genes) were involved in breast pathogenesis 20 . Researchers also demonstrated that aberrant methylated genes played various functions in the cell cycle regulation, proliferation and adhesion 21 . Research of Jelilek J showed that aberrant DNA methylation is associated with CML progression 22 .…”
Section: Discussionmentioning
confidence: 99%